The Potential of Economic Base of the Livestock Sector in Kediri-East Java - Nur Solikin; Budi Hartono; Zaenal Fanani; M Nur Ihsan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2018)
Purpose of this study is to describe the potential of economic base of livestock commodities in Kediri-East Java- Indonesia. The research was conducted from March 2017 by using exploratory method, referring to secondary data in Statistic Centers publication of Kediri Regency. Location Quotient Analysis (LQ) data analysis was usedto determine the economic base of livestock sector in Kediri Re-gency. The results of the research are identified as follows: 1) Sub-district Base of beef cattle live-stock that is located in Mojo, Semen, Ngadiluwih, Ngancar, Plosoklaten, Gurah, Kunjang, Plemahan, Purwoasri, Papar, Pagu, KayenKidul, Gampengrejo, Ngasem, Banyakan, Grogol , and Tarokan. 2) Districts of dairy cattle commodity base include Ngancar, Plosoklaten, Kandangan, KayenKidul, and Gampengrejo. 3) Subdistrict base of buffalo cattle commodity include Mojo, and Ngadiluwih, Ke-pung, Kandangan, Badas, Kunjang, Gampeng, Ngasem, and Grogol. 4) The sub-districts of horse livestock commodities include Mojo, Semen, Kandangan, Kunjang, Plemahan, Gampengrejo, Ban-yakan, Grogol, and Tarokan. 5) Sub-district of pigs commodity base include Wates, Ngancar, Gamp-engrejo, and Banyakan sub-districts. 6) The districts of goats / sheep bases include Mojo, Semen, Kras, Ngancar, Plosoklaten, Gurah, Kepung, Kandangan, Kunjang, Plemahan, Purwoasri, Papar, Pa-gu, Kayenkidul, Gampengrejo, Ngasem, Banyakan, Grogol, and Tarokan. 7) The sub-districts of the commodities of chicken breeds include Mojo, Semen, Ngadiluwih, Kras, Gurah, Kepung, Kandangan, Kunjang, Plemahan, Purwoasri, Papar, Pagu, KayenKidul, Gampengrejo, Ngasem, Banyakan, Grogol, and Tarokan. 8) Sub-districts of commodities of chicken breeds include Kras, Ringinrejo, Kandat, Wates, Plosoklaten, Puncu, Pare, and Badassubdistricts. 9) The districts of livestock com-modity base include Mojo, Semen, Ngadiluwih, Kandat, Ngancar, Kandangan, Badas, Plemahan, Pa-gu, Gampengrejo, Ngasem, Banyakan, Grogol and Tarokansubdistricts. 10) Rabbit livestock com-modity base covers the sub-districts of Semen, Kras, Ngancar, Plosoklaten, Gurah, Kepung, Kan-dangan, Gampengrejo, Ngasem, Banyakan and Grogol.